Analyzing Students’ Obstacles of Online Learning for UIB English Class - Leil Badrah Zaki; Destrin Destrin (Edu-Ling: Journal of English Education and Linguistics, 2021)
Online learning is used because of the Covid-19 virus outbreak and the lecturers and students must use online platform to teach the students. As for the learning, online platforms may have some benefits and problems either for students and lecturers. UIB have implemented the online learning by using Microsoft Teams and Moodle. This research are sought to find what are the students obstacles with online learning in UIB. The subjects of this research are 335 UIB students from 1st semester English class 1 students batch 2020/2021. This research used quantitative approach which of collecting data that yield results such as words or pictures. The data collection used questionnaire that spreaded to 335 UIB students from all major via social media: Whatsapp, Line, etc. This research has 6 lists of obstacles from various researchers which are: Lack of interest, Lack of motivation, Lack of digital devices, Lack of competence in using technology, Role of motivation, and English curriculum. The list of obstacles will be explained in this research to find the similarly comparison from the various researchers with this research. The result of the research could become a suggestion from the students' view for the UIB in conducting the online learning. The suggestions for UIB are repair the LMS server so that the students can submit or download the learning materials without any problem. Then, maybe for the LMS application can add some new features such as notification for the assignment deadline; sort and separate the list of learning materials and assignment from all major so the students can find the learning materials and their assignment easily. Also, increase the file capacity for submitting assignment, material file or video assignment will make the students easier to submit their assignment without have to redo the work to adjust the size of file to submit it on LMS.